2008
DOI: 10.3748/wjg.14.1741
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in hepatocellular carcinoma

Abstract: As for many other tumors, development of hepatocellular carcinoma (HCC) must be understood as a multistep process with accumulation of genetic and epigenetic alterations in regulatory genes, leading to activation of oncogenes and inactivation or loss of tumor suppressor genes (TSG). In the last decades, in addition to genetic alterations, epigenetic inactivation of (tumor suppressor) genes by promoter hypermethylation has been recognized as an important and alternative mechanism in tumorigenesis. In HCC, aberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
147
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 88 publications
3
147
1
1
Order By: Relevance
“…21 In general, cancer cells have global hypomethylation, but they have hypermethylation in some specific genes. DNA hypermethylation in promoter regions is associated with silencing of tumor suppressor genes because of direct or indirect prevention to accessing transcription factors in the promoter region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In general, cancer cells have global hypomethylation, but they have hypermethylation in some specific genes. DNA hypermethylation in promoter regions is associated with silencing of tumor suppressor genes because of direct or indirect prevention to accessing transcription factors in the promoter region.…”
Section: Discussionmentioning
confidence: 99%
“…DNA hypermethylation in promoter regions is associated with silencing of tumor suppressor genes because of direct or indirect prevention to accessing transcription factors in the promoter region. 22 Recent studies 21,23,24 have demonstrated that CpG island hypermethylation, via silencing of key cancer-related genes, plays a major causal role in cancer, including HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the HCV genome is not controlled by epigenetic factors such as DNA methylation or histone modifications. Nonetheless, this virus has been found to be associated with aberrant host gene promoter methylation in HCC (Tischoff and Tannapfe, 2008).…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…In the case of HBV, chronic inflammation and accumulation of genetic alterations in infected hepatocytes induced by the host (Cougot et al, 2005;Gurtsevitch, 2008) and epigenetic alterations produced by viral proteins (Tischoff and Tannapfe, 2008;Herceg and Paliwal, 2009;Shon et al, 2009;Zheng et al, 2009) are mainly responsible for the carcinogenesis induced by HBV.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…28,31 have been reported and recently reviewed. 32,33 In a study using 15 hepatoma cell lines after treatment with decitabine, epigenetic silencing through hypermethylation of scavenger receptor class A, member 5 (SCARA5) was observed and confirmed in a panel of human HCC samples. 34 Here, we have performed an array-based methylation analysis on 27,578 methylation sites in 13 primary HCC samples in comparison to nontumorous cirrhotic tissue (n ¼ 17) and normal liver (n ¼ 12).…”
mentioning
confidence: 98%